O caso Quincas Borba - Coelho, Maria Rita Vieira (2010)
The meanders of the nineteenth century correspond to a period in which both the bourgeois institutions and the aristocracy started adopting bourgeois values and practices that replace institutions which were impregnated with feudal and clerical remnants to consolidate themselves into a capitalist production order, within a patriarchal society organization, and on the conception of liberal State which legitimated and legalized them, and live together with the criticism of state of affairs consisting of that order of production, its social organization and conception of the respective State. An example of that criticism is found on the plot of Quincas Borba, a work that develops the theme of stimulated madness which takes into account the existence and corruption of legal treat addressed to the phenomenon of insanity.The end of those to whom it is attributed insanity is to live in misery, whatever it may be, the dispossession of inherited wealth, to gether with restriction to the access to property, both made possible by legal manipulation sketched on the plot, leading them to the lack of social life, and ultimately to death. That's what happened to Rubião. Humanitas was confirmed.